Karakteristik Manuskrip Al-Qur`an Koleksi Kesultanan Kutaringin Kotawaringin Barat Kalimantan Tengah - Nunuk Rima Aini; Ahmad Fathoni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to uncover the characteristics of the Al-Qur'an manuscripts in the collection of the Sultanate of Kutaringin at the Mangkubumi Palace, with a specific focus on the textual aspect. The characteristics of the mushaf will be identified through the analysis of the verse texts and other related aspects based on the theories within ‘Ulūmul Qur`ān (the sciences of the Qur`an). This research combining a literature-based and a field-based methods. The combination of these methods is necessary when the data is not sufficiently representative to draw conclusive findings. The research design is qualitative, aiming to obtain a comprehensive understanding of this particular aspect. The primary data source of this research is the seventh volume of the mushaf in Mangkubumi Palace and other related secondary data sources. The results of this research indicate that the Qur’an manuscript of Kutaringin Sultanate in Mangkubumi Palace, especially the seventh mushaf have identical characteristics to the style of Ottoman Turkish manuscripts. This showed on the writing of some diacritical mark aspects (ḍabṭ), the markings for dividing of the Qur’an (ḥizb), the calligraphy and the mushaf illumination that clearly using Turkish writing style. This mushaf, written in the early 19th century, was transcribed using a mixed rasm (written form or script of an Arabic calligraphy text) style, namely the rasm ‘uṡmānī and the rasm imlā`ī, and consistently written with the qirā`āt ‘Āṣim riwayat Ḥafṣ.